Using Continuing Professional Development (CPD) for Enhancing Teaching Quality in Higher Education of Bangladesh - Rozina Afroz; Suria Selasih Angit Asra Ramlan; Nusrat Zerin Anny; Md. Nurul Islam Afroz (Global READ Center, 2024)
Bangladesh is crossing milestones in achieving sustainability in every sector and one of the most important sectors is the higher education sector. Thus, it is advisable to improve the quality of education in the environment by evaluating some parameters of service quality. This paper examines the quality of teaching in the higher education sector through continuing Professional Development (CPD) and examines the important role that teachers play in contributing to the development of the knowledge and values needed for teachers. However, since the study is on descriptive and analytical case studies and literature reviews based on reliable sources which shows that workshops and seminars are effective in most traditional modes has as proved to be insufficient for Coordination and evaluation of programs should be mandatory for professional development, which will help to maintain a positive environment with changing global situation. This paper identifies the definition, the dimension, the model, effectiveness, and types of CPD, the quality of service related to student satisfaction. The study helps to identify and assist in taking steps to address the lack of teaching quality whether teachers receive continuous professional development programs and whether such programs are adequate in our college.